Defining the Reliability of Deltoid Reanimation by Nerve Transfer When Using Abnormal but Variably Recovered Triceps Donor Nerves - Ferris, Scott; Withers, Aaron; Shukla, Lipi (Frontiers in Surgery, 2021)
Upper brachial plexus injuries to the C5/6 roots or axillary nerve can result in severe deficits in upper limb function. Current techniques to reinnervate the deltoid muscle utilise the well described transfer of radial nerve branches to triceps to axillary nerve. However, in around 25% of patients, there is failure of sufficient deltoid reinnervation. It is unclear in the literature if deltoid reanimation should be attempted with a nerve transfer from a weak but functioning triceps nerve. The authors present the largest series of triceps to axillary nerve transfers for deltoid reanimation in order to answer this clinical question. 77 consecutive patients of a single surgeon were stratified and analysed in four groups: 1) normal triceps at presentation, 2) abnormal triceps at presentation recovering to clinically normal function preoperatively, 3) abnormal triceps at presentation remaining abnormal preoperatively and lastly 4) where pre-operative triceps function was deemed insufficient for use, requiring alternative reconstruction for deltoid reanimation. The authors considered deltoid re-animation of M4 as successful for the purpose of this study. Median MRC values demonstrate group 1 achieves this successfully (M5), whilst median values for groups 2-4 result in M4 power (albeit with decreasing interquartile ranges). Median post-operative shoulder abduction AROM values were represented by 170(85-180) in group 1, 117.5(97.5-140) in group 2, 90(35-150) in group 3 and 60(40-155) in group 4. For both post-operative assessments, subgroup analyses demonstrated statistically significant differences when comparing group 1 with group 3 and 4 (p<0.05), whilst all other group to group pairwise comparisons did not reach significance. The authors postulated that triceps deficiency can act as surrogate marker of a more extensive plexus injury and may predict poorer outcomes if weakness persists representing trending differences between groups 2 and 3. However, given no statistical differences were demonstrated between groups 3 and 4, authors conclude utilising an abnormal triceps nerve, that demonstrates sufficient strength and redundancy intraoperatively, is preferable to alternative transfers for deltoid reanimation. Lastly, in group 4 patients where triceps nerves are unusable for nerve transfer, alternative operations can also achieve sufficient outcomes and should be considered for restoration of shoulder abduction.